2015
DOI: 10.1038/srep15086
|View full text |Cite
|
Sign up to set email alerts
|

Determining the N-terminal orientations of recombinant transmembrane proteins in the Escherichia coli plasma membrane

Abstract: In silico algorithms have been the common approach for transmembrane (TM) protein topology prediction. However, computational tools may produce questionable results and experimental validation has proven difficult. Although biochemical strategies are available to determine the C-terminal orientation of TM proteins, experimental strategies to determine the N-terminal orientation are still limited but needed because the N-terminal end is essential for membrane targeting. Here, we describe a new and easy method t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Although it is well-attested that fusion proteins can support the expression of synthetic transmembrane segments, it is less clear that this extends to standalone de novo sequences and examples are relatively scarce. The available evidence is that redesigned and de novo proteins comprised of a limited selection of hydrophobic amino acids (mainly L, I and A) can generally be expressed by the cell 11 , 22 , 23 , 40 and localized to the plasma membrane 11 , 22 , 23 . Goparaju and colleagues 40 used a fusion protein strategy to deliberately express a minimal de novo protein into inclusion bodies, so the intrinsic localization of that sequence is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is well-attested that fusion proteins can support the expression of synthetic transmembrane segments, it is less clear that this extends to standalone de novo sequences and examples are relatively scarce. The available evidence is that redesigned and de novo proteins comprised of a limited selection of hydrophobic amino acids (mainly L, I and A) can generally be expressed by the cell 11 , 22 , 23 , 40 and localized to the plasma membrane 11 , 22 , 23 . Goparaju and colleagues 40 used a fusion protein strategy to deliberately express a minimal de novo protein into inclusion bodies, so the intrinsic localization of that sequence is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A logical extension of this approach is to develop new minimal systems that are geared towards a deeper understanding of oligomeric and multipass transmembrane proteins. It has already been shown that bottom-up designs with very low sequence complexity can be tolerated by the cell 11 , 22 , 23 , but it is not yet clear whether these simplistic proteins can bridge the gap between being both resident in cellular membranes and compatible with the in vitro biophysical methods necessary for protein characterization. A reasonable design target for such a protein would be a tetrahelical bundle, which is a common motif in natural membrane proteins and can support various functions 2 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Both BAQ32849 and BAQ33018 were localized in the cytoplasm with PSORT and in the cell membrane with Gpos-mPLoc (more details in Supplementary Table S2 ). In the literature, it is common to find discrepancies between the in silico -predicted topology and the experimental data ( Rodriguez-Ortega et al, 2006 ; Lee et al, 2015 ). We only found two discrepancies when comparing the characteristic motifs of surface-exposed proteins predicted using bioinformatics tools with the mapping of the MS identified peptides on the primary sequence of the proteins (Supplementary Table S1 and Supplementary Data).…”
Section: Discussionmentioning
confidence: 99%